ANALISIS PENGARUH ARBITRASE TERHADAP PERGERAKAN NILAI TUKAR MATA UANG - , Kun Arif Cahyantoro, ST ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Arbitration is generally defined as the price discrepancy triggered by the imbalance price. In general, the LOP (Law of One Price) are applied to all financial markets which would not have a chance to do the arbitration. Empirical evidence on triangular arbitrage againts several currency pairs using co-integration analysis approach to asset pricing matrix of pairs of data exchange (currency pairs) indicated that the benefit to arbitration is likely to occur when the market deviates from power parity theory buy (purchasing power parity theory) and the equilibrium exchange rate. These imbalances affect the movement of currency exchange rate.